Respuesta :

Answer:

[tex]a = -9[/tex]

[tex]b = 4[/tex]

Step-by-step explanation:

Given

Sequence: a+3b, a+7b, a+11b

2nd term = 19

5th term = 67

Required

Find a and b

First, the 5th term needs to be calculated;

Using formula for Arithmetic Progression (AP), the formula goes thus

[tex]T_n = T_1 + (n - 1)d[/tex]

Where n = 5

T_1 = a + 3b ------------ FIrst term

[tex]d = T_2 - T_1 or T_3 - T_2[/tex] --- Difference between two successive terms

[tex]d = a + 7b - (a + 3b)[/tex]

[tex]d = a + 7b -a - 3b[/tex]

[tex]d = a - a + 7b - 3b[/tex]

[tex]d = 4b[/tex]

So, [tex]T_n = T_1 + (n - 1)d[/tex] becomes

[tex]T_5 = a + 3b + (5 - 1)4b[/tex]

[tex]T_5 = a + 3b + (4)4b[/tex]

[tex]T_5 = a + 3b + 16b[/tex]

[tex]T_5 = a + 19b[/tex]

Now that we have values for 2nd and 5th term;

From the second, T2 = 19 and T5 = 67

This gives

[tex]a + 7b = 19[/tex] --- Equation 1

[tex]a + 19b = 67[/tex] ---- Equation 2

Make a the subject of formula in (1)

[tex]a = 19 - 7b[/tex]

Substitute these values in equation 1

[tex]a + 19b = 67[/tex] becomes

[tex]19 - 7b + 19b = 67[/tex]

[tex]19 + 12b = 67[/tex]

Collect like terms

[tex]12b= 67 - 19[/tex]

[tex]12b = 48[/tex]

Divide both sides by 12

[tex]\frac{12b}{12} = \frac{48}{12}[/tex]

[tex]b = 4[/tex]

Recall that b = 4

Substitute a = 19 - 7b and nothing will hire

[tex]a = 19 - 7(4)[/tex]

[tex]a = 19 - 28[/tex]

[tex]a = -9[/tex]

Hence, the values of a and b are -9 and 4 respectively.

Answer:
a= - 9
b= 4
Step-by-step explanation:

From +3b to 7b it's add 4 (so I used this rule to find the next 2 terms.)

4rd term is a + 15b
5 term is a + 19b = 67

create a simultaneous equation between the 2nd & 5th term - since, we know what it's equal to.
a + 19b = 67
a +7b = 19
(same signs/operation of + so subtract to cancel a)

a-a =0
19b - 7b = 12b
67 - 19 =48


0 + 12b = 48
÷12 both sides
b = 4

Substitute, b= 4 into one equation(either from the 2nd or 5th term equation):

a+ 7b=19
a + 7 x 4 = 19
a + 28 = 19
- 28
a= - 9

Hope this helps!